2020
DOI: 10.1001/jamanetworkopen.2020.28627
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trends in Second Primary Cancers in Patients With Metastatic Melanoma From 2005 to 2016

Abstract: Key Points Question When compared with prior therapies, are immune checkpoint inhibitors for metastatic melanoma associated with development of second primary cancers? Findings In this cohort study of 5016 patients with metastatic melanoma between 2005 and 2016, the overall risk of second primary cancers increased after the introduction of immune checkpoint inhibitors. Risks for cancer of the small intestine and myeloma were higher than before the era of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…In comparison, population‐based genetic testing among breast cancer survivors identified PVs in 5.0% of case patients and 1.63% of controls, 38 and in a universal genetic testing model for patients with cancer, 8.1% (242 of 2984) were identified as harboring a PV in 1 of the 21 genes ( ATM , BARD1 , BRCA1 , BRCA2 , BRIP1 , CDH1 , CHEK2 , EPCAM , MLH1 , MSH2 , MSH6 , biallelic MUTYH , NBN , NF1 , PALB2 , PMS2 , PTEN , RAD51C , RAD51D , STK11 , and TP53 ) 19 . Identifying patients with germline PVs is crucial to their care, including cancer treatment and cancer surveillance for a subsequent cancer diagnosis 39 . Emerging data suggest that patients with a subsequent cancer diagnosis have worse outcomes than patients with an initial cancer diagnosis among most cancer types 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, population‐based genetic testing among breast cancer survivors identified PVs in 5.0% of case patients and 1.63% of controls, 38 and in a universal genetic testing model for patients with cancer, 8.1% (242 of 2984) were identified as harboring a PV in 1 of the 21 genes ( ATM , BARD1 , BRCA1 , BRCA2 , BRIP1 , CDH1 , CHEK2 , EPCAM , MLH1 , MSH2 , MSH6 , biallelic MUTYH , NBN , NF1 , PALB2 , PMS2 , PTEN , RAD51C , RAD51D , STK11 , and TP53 ) 19 . Identifying patients with germline PVs is crucial to their care, including cancer treatment and cancer surveillance for a subsequent cancer diagnosis 39 . Emerging data suggest that patients with a subsequent cancer diagnosis have worse outcomes than patients with an initial cancer diagnosis among most cancer types 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of ICIs on second primary tumors is not yet clear. Heudel et al concluded that ICIs could reduce the incidence of second primary tumors, 6,7 while Deng et al found an increased overall risk of second primary cancer after the introduction of ICIs to the treatment of melanoma 8 . In theory, the immune effect activated by ICIs is systemic and should be able to produce an offensive effect against all types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Heudel et al concluded that ICIs could reduce the incidence of second primary tumors, 6 , 7 while Deng et al found an increased overall risk of second primary cancer after the introduction of ICIs to the treatment of melanoma. 8 In theory, the immune effect activated by ICIs is systemic and should be able to produce an offensive effect against all types of tumors. However, patients who benefit from ICIs tend to have higher TMB, implying a higher frequency of genetic mutations than normal.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Heudel et al, patients treated with ICI for a first primary cancer had reduced risk of MPM, compared to those treated with chemotherapy [ 26 ]. In contrast, a SEER-based study comparing melanoma patients from the pre- and post-ICI eras (2005-2010 and 2011-2016, respectively), found that patients from the later period had more MPM [ 27 ]; however, the authors did not report whether patients received ICI or not (PD-1 inhibitors were approved in 2014), but rather looked at differences by date of treatment alone.…”
Section: Discussionmentioning
confidence: 99%